Bayesian phylogeny analysis of vertebrate serpins illustrates evolutionary conservation of the intron and indels based six groups classification system from lampreys for ∼500 MY - Kumar, Abhishek (PeerJ, 2015)
The serpin superfamily is characterized by proteins that fold into a conserved tertiary structure and exploits a sophisticated and irreversible suicide-mechanism of inhibition. Vertebrate serpins are classified into six groups (V1–V6), based on three independent biological features—genomic organization, diagnostic amino acid sites and rare indels. However, this classification system was based on the limited number of mammalian genomes available. In this study, several non-mammalian genomes are used to validate this classification system using the powerful Bayesian phylogenetic method. This method supports the intron and indel based vertebrate classification and proves that serpins have been maintained from lampreys to humans for about 500 MY. Lampreys have fewer than 10 serpins, which expand into 36 serpins in humans. The two expanding groups V1 and V2 have SERPINB1/SERPINB6 and SERPINA8/SERPIND1 as the ancestral serpins, respectively. Large clusters of serpins are formed by local duplications of these serpins in tetrapod genomes. Interestingly, the ancestral HCII/SERPIND1 locus (nested within PIK4CA) possesses group V4 serpin (A2APL1, homolog of α2-AP/SERPINF2) of lampreys; hence, pointing to the fact that group V4 might have originated from group V2. Additionally in this study, details of the phylogenetic history and genomic characteristics of vertebrate serpins are revisited.
Keywords: Vertebrates; Serpins; Bayesian phylogeny; Gene structure; Gene duplication; Intron-exon